Management of Hyperactive Delirium in the Pediatric Intensive Care Unit: Case Series of Three Young Children - Jesus, Anna O.; Jones, Lotte; Linares, Rebecca; Buck, Marcia L.; Frank, Deborah U. (Journal of Pediatric Intensive Care, 2020)
Children in the intensive care unit (ICU) are at high risk of developing delirium, given their underlying disease processes, the adverse effects of treatments and medications, and the stressful, abnormal environment. If prevention and nonpharmacologic measures to treat delirium are unsuccessful, atypical antipsychotics are considered, although they are not approved by Food and Drug Administration for the treatment of pediatric delirium and could have significant adverse side effects. This case report presents three pediatric patients with hyperactive ICU delirium that risked life-threating complications who were successfully treated with short courses of atypical antipsychotic medications.
Keywords: pediatric; delirium; antipsychotic